Using a portable near-infrared spectroscopy device to estimate the second ventilatory threshold - Rodrigo-Carranza, V.; González-Mohíno, F.; Turner, A. P.; Rodriguez-Barbero, S.; González-Ravé, J. M. (International Journal of Sports Medicine, 2021)
A breakpoint in a portable near-infrared spectroscopy (NIRS) derived deoxygenated haemoglobin (deoxy[Hb]) signal during an incremental VO2max running test has been associated with the second ventilatory threshold (VT2) in healthy participants. Thus, the aim was to examine the association between this breakpoint (NIRS) and VT2 in well-trained runners. Gas exchange and NIRS data were collected during an incremental VO2max running test for 10 well-trained runners. The breakpoint calculated in oxygen saturation (StO2) and the VT2 were determined and compared in terms relative to %VO2max, absolute speed, VO2, and maximum heart rate (HRmax). There were no significant differences (p>0.05) between the breakpoint in StO2 and VT2 relative to %VO2max (87.00±6.14 and 88.28 ± 3.98 %), absolute speed (15.70±1.42 and 16.10±1.66 km·h-1), VO2 (53.71±15.17 and 54.66±15.57 ml·kg-1·min-1), and%HRmax (90.90±4.17 and 91.84±3.70%). There were large and significant correlations between instruments relative to%VO2max (r=0.68, p<0.05), absolute speed (r=0.86, p<0.001), VO2 (r=0.86, p<0.001), and %HRmax (r=0.69; p<0.05). A Bland and Altman analysis of agreement between instruments resulted in a mean difference of - 1.27±4.49%, -0.40±0.84 km·h-1,-0.90±3.07 ml·kg-1·min-1, and - 0.94±3.14 for %VO2max, absolute speed, VO2, and %HRmax, respectively. We conclude that a portable NIRS determination of the StO2 breakpoint is comparable with VT2 using gas exchange and therefore appropriate for use in determining exercise training above VT2 intensity. This is the first study to analyze the validity with the running mode using a NIRS portable device.